Production of biosurfactants by bacteria collected in soil contaminated by diesel oil on the Antarctic Continent (Research, Society and Development, 2022)
Currently, the whole world strives for a sustainable development to avoid the depletion of natural resources. Therefore, the search for new biotechnological products such as biosurfactants has generated interest due to its low toxicity, biodegradability and ecological acceptability. Furthermore, biosurfactants have several applications such as emulsification, wettability, foaming, cleaning, and reduction of crude oil viscosity. The objective of this work was to identify the bacteria collected in Antarctica and evaluate their capacity to produce biosurfactants. In this study, bacteria collected in diesel contaminated soil around the Comandante Ferraz Antarctic Station were identified (Rhodococcus erythropolis, Rhizobium radiobacter, Microbacterium liquefacien, Pseudomonas libanensis and Pseudomonas veronii) and analyses were carried out to confirm whether these bacteria produce biosurfactants. Interestingly, the compounds isolated from the bacteria showed droplet propagation and reduced the surface tension of the water, which are properties of biosurfactants. Furthermore, these compounds showed carbohydrates in their molecular composition. Given these findings, these species have potential application in biotechnological areas, such as bioremediation of environments contaminated by diesel oil and in cosmetic and personal care as emulsifier. In addition, the use of diesel oil waste by bacteria as a carbon source becomes an attractive alternative because it reduces environmental contamination and has a low cost.